Reframing the Qlipoth in Digital Media A Mythological Study of Qlipoth in Honkai Star Rail - Fawas Mubarok Azzuhdi (CV. Ulil Albab Corp, 2026)
This study examines the transformation of Qlipoth, the Aeon of Preservation in Honkai: Star Rail, by comparing its in game representation with the traditional Qlipoth found in Kabbalistic mysticism. The research aims to understand how the game reconstructs a myth that originally negative into a positive. Using mythological criticism as the core analytical approach, the study combines interpretations of traditional sources with narrative and data from the game, including lore entries and Simulated Universe encounters. The analysis is supported by three theoretical perspectives. Campbell’s concept of myth reconstruction explains how mythic figures are reshaped to meet contemporary cultural needs. Hall’s representation theory shows how the game encodes new symbolic meanings that transform impurity into preservation. Jenkins’ framework of transmedia storytelling reveals how Qlipoth’s mythic identity is built through multiple narrative layers. The results show that Honkai: Star Rail does not merely borrow mythological elements but actively reinterprets them to construct a coherent and modern digital cosmology. This reinterpretation demonstrates how digital media create contemporary forms of mythology by reshaping ancient symbols for modern audiences.